The Students’ Perception on Online and Offline Reading in English Education Department of Universitas Muhammadiyah Yogyakarta - Upik Maria Ulfah (PBI 15 UMY 068, 2015)
*68 Students often get assignment to read journal articles in Online or Offline text types. Besides, the design types of reading assignment that the students get may affect students’ preferences on the online and offline reading. This study aims to find out students’ perception on online and offline reading at English Education Department of Universitas Muhammadiyah Yogyakarta. This study used qualitative research design and specifically employed descriptive qualitative research. The researcher chose interview as the instrument to gather the data. There were six (6) participants coming from students’ of EED of UMY from batch 2011. Participants were chosen by doing random sampling. In analyzing the data, the researcher used three kinds of coding including open coding, axial coding, and also selective coding to get final categorization of the data. Prior to it, the researcher had already done member checking to get validity of the data before analyzing the data. The first purpose of this study revealed the students’ of EED UMY preference on online and offline reading. The second purpose of this study showed the possible causes related to the students’ of EED UMY preferences on online and offline reading. Based on finding from the interview, it was revealed that students’ of English Education Department of UMY prefer offline reading. The result of the research showed that, there were three possible causes on online reading and five possible causes on offline reading. The possible causes on offline reading included capability to take a note and underlining, portability, eye sight, reading position and flexibility. In addition, the causes of online reading were capability to take a note, reading position and tools. However, among those possible causes, capability to take a note and eyesight became the causes which mostly influenced students’ preferences on online and offline reading.